The Effectiveness of Classical Guidance in Increasing Drug Resistance Among Adolescents at Pusat Pengembangan Anak Gereja Kristen Perjanjian Baru Pematangsiantar - Rosmala Dewi; Daniel Sitorus (Insight: Journal of Counseling and Psychology, 2026)
This research examines the effectiveness of classical guidance services in enhancing adolescents’ resistance to drugs at the Child Development Center of the Gereja Kristen Perjanjian Baru Pematangsiantar. The study employed a Guidance and Counseling Action Research (PTBK) design implemented in two cycles. The participants consisted of 20 adolescents aged 12–15 years. Data were collected through a drug-resistance questionnaire, observations, and interviews. The findings showed that the average drug-resistance score increased from 75 (69%) in the pre-cycle to 89 (81%) in Cycle I, and further improved to 104 (95%) in Cycle II. The Paired Sample t-Test revealed a significant difference between the pre- and post-intervention scores. These results indicate that classical guidance services are effective in strengthening adolescents’ resistance to drugs. The intervention not only improved their knowledge and awareness of drug risks, but also fostered assertiveness, personal commitment, and the ability to refuse drug offers firmly yet courteously.